A causalidade de porque em textos escolares: domínios de atuação, gêneros de produção - Soncin, Geovana [UNESP]; Longhin, Sanderleia Roberta [UNESP] (My University, 2014)
In this article we address the causality conveyed by constructions with porque in compositions written by students from a public school. Our purpose is to compare factors of cognitive and discursive order for examining possible motivations related to the variability and to the complexity involved in causal constructions. The analysis that we propose assumes that porque may have different interpretations depending on the context of use and may indicate the cause of an actual event, or the cause of a belief, or the cause of a speech act. We consider some theses of ontogenetic nature that support that the most cognitively complex meanings appear later, but we hold that there are other issues at stake. In what follows, we present evidence that the emergence of different causal relations with porque also takes place as a result of the operation of discourse genres.

Neste artigo, tratamos da causalidade veiculada pelas construções com porque em textos escolares, com o propósito de equacionar a relevância de fatores de ordem cognitiva e de ordem discursiva para a investigação das motivações acerca da realização variável e da complexidade envolvidas nas construções causais. Partimos da constatação de que porque é passível de diferentes interpretações, a depender do contexto de uso, podendo sinalizar a causa de um evento real, a causa de uma crença e a causa de um ato de fala. Contemplamos teses de natureza ontogenética que sustentam que os significados cognitivamente mais complexos são mais tardios, mas defendemos que há outros fatores em jogo. Apresentamos evidências de que a emergência de diferentes relações causais com porque se configura também em função do funcionamento dos gêneros de discurso.
Keywords: Junção; Causalidade; Escrita; Junction; Causality; Writing